Reduction behaviour of iron ore pellets using hardwood biomasses as a reductant for sustainable ironmaking - Singh A.K.; Mishra B.; Kumar S.; Sinha O.P.; Singh R. (My University, 2025)
Renewable biomass is a potent, CO2 neutral substitute to fossil coal and coke in iron making. However, there has been relatively little work on the utilization of biomass for the production of directly reduced iron (DRI). The aim of the present work is to characterize Acacia nilotica (W1), Albizia lebbeck (W2), and Leucaena leucocephala (W3) biomass and to reduce iron ore pellets primarily with the volatile matter from the wood at high temperature, yielding charcoal simultaneously as a co-product. The chemical, physical, and mechanical properties of the three biomass species were investigated. Effect of different biomasses and reduction parameters like C/O ratio, reduction temperature, and time on %Reduction (%R) was studied. DRI was characterized using %Metallization (%M), XRD, and SEM. Up to 89% reduction was achieved in the simultaneous carbonization of biomass and the reduction of iron ore pellets at a temperature of 1000 °C. The pellets cooled in the furnace after reduction resulted in lower %R (e.g., W1:57%, W2:54%, and W3:63%) than the respective air-cooled pellets (e.g., W1:88%, W2:83%, and W3:86%). Oxidation was the cause for lower %R in furnace cooled (slow cooling) reduction experiments than in the air cooled. Co-produced wood charcoal after the reduction of iron ore contained approximately 76–81% carbon which competes well with a typical value for coal of 70%. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2022.